Significance of Islam Nusantara Values in an Indonesian Multicultural Society - Setiawan, David Eko; Stevanus, Kalis (Journal of Al-Tamaddun, 2023)
Indonesian society is plural, consisting of various cultures, religions, beliefs, and ethinicities. All these differences can trigger fanaticism, causing tension and conflict in society. This paper uses the literature method to describe the values contained in Islam Nusantara (Indonesian model of Islam). The results of the literature review show that Islam Nusantara values can act as an alternative and mediator when there is a conflict of differences, since it prioritize a high appreciation of plurality as a social reality. Islam Nusantara can drive social ethics to foster tolerance and social solidarity in a multicultural society like Indonesia.